Evaluation of 3D high resolution images using inexpensive distributed parallel system: Application fields on medical images - Eren, Haluk; Çelik, Ümit; Poyraz, Mustafa (My University, 2007)
In the telesurgery operations, images should be high resolution and processed in real time. It seems difficult to accomplish this process in real time using only one computer. In our study, we propose to get 3d scene images inside and outside of surgery environment in real time and transfer them into different places. As known, 3d reconstruction needs intensive calculations. Nowadays, using distributed parallel systems are getting increase. Therefore, we investigate the performance rates using a group of inexpensive inert computers which work as a distributed parallel system supposed to be established in a medical environment.
Düşük maliyetli da?itik paralel sistem kullanarak 3B yüksek çözünürlüklü i?mgelerin de?erlendirilmesi: Medikai görüntüler üzerinde u?ygulama alanlari
2007 IEEE 15th Signal Processing and Communications Applications, SIU -- 11 June 2007 through 13 June 2007 -- Eskisehir -- 73089
Keywords: Image enhancement; Image reconstruction; Signal processing; Surgery; 3-D reconstructions; 3D scenes; Application fields; High resolutions; High-resolution images; Medical imaging; Parallel systems; Real time; Telesurgery; Three dimensional